Jesus of Nazareth message and history - Gnilka, Joachim, 1928-; Schatzmann, Seigfried S. (Peabody, MA Hendrickson, 1997)
Includes bibliographical references, Scripture index and other index.
Original edition: Jesus von Nazaret: Botschaft und Geschichte. C Verlag Herder, Freiberg im Breisgau, 1993.
Keywords: Jesus Christ -- biography -- public life; Jesus Christ -- teachings